Neuroprotective effect of Annona muricata-derived polysaccharides in neuronal HT22 cell damage induced by hydrogen peroxide. Issue 5 (3rd May 2020) - Kim, Woo Sik; Kim, Yi-Eun; Cho, Eun-Ji; Byun, Eui-Baek; Park, Woo Yong; Song, Ha-Yeon; Kim, Kwangwook; Park, Sang-Hyun; Byun, Eui-Hong
ABSTRACT: Crude extracts and phytochemical compounds derived from Annona muricata leaves have been demonstrated to exert neuroprotective effects. However, the neuroprotective effects of Annona muricata leaves-derived polysaccharide extracts (ALPs) have not been investigated. ALP treatment was shown to induce concentration-dependent antioxidant activity in HT22 cells, and to increase cell viability in H2 O2 -treated HT22 cells. These effects were correlated with a decrease in major components of oxidation, including: Ca 2+, ROS, and malondialdehyde (MDA). Mediators of the intracellular response to oxidation, including Bax, cytochrome c, and cleaved caspases-3, -8, -9, MAPKs, and NF-κB, were positively influenced by ALP treatment under conditions of H2 O2 -mediated oxidative stress. In addition, ALP restored the expression of superoxide dismutase (SOD) and associated signaling pathways (PARP, PI3K/AKT and Nrf2-mediated HO-1/NQO-1) following H2 O2 treatment. These results provide new pharmacological evidence that ALP facilitates neuroprotection via prevention of neuronal oxidative stress and promotion of cell survival signaling pathways. Abbreviations: ABTS: 2, 2ʹ-azino-bis-(3-ethylbenzothiazoline-6-sulfonicacid); AD: Alzheimer's disease; ALP: polysaccharide extracts isolated from Annona muricata leaves; ARE: antioxidant response element; DPPH: 1, 1-diphenyl-picrylhydrazyl; DCFH-DA: 2ʹ, 7ʹ-dichlorofluorescin diacetate; ECL: electrochemiluminescence; ERK: extracellular regulated kinase; FBS: Fetal bovine serum; FITC: fluorescein isothiocyanate; FRAP: ferric reducing antioxidant power; HO-1: Heme oxygenase-1; JNK: c-jun N-terminal kinase; MAPKs: mitogen-activated protein kinases; MDA: malondialdehyde; MMP: mitochondrial membrane potential; MTT: 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazoliumbromide; NQO1: NAD(P)H:quinine oxidoreductase 1, Nrf2: nuclear factor-E2-related factor 2; PD: parkinson's disease; PI3K: phosphatidylinositol-3kinase; PVDF: polyvinylidene difluoride; ROS: reactive oxygen species; SOD: Superoxidedismutase; TPTZ: tripydyltriazine GRAPHICAL ABSTRACT: uf0001 Proposed mechanism of the neuroprotective activity induced by ALP in H2 O2 -treated HT22 hippocampus cells.